This is not Lynch syndrome: lessons from misattributed diagnoses in constitutional mismatch repair deficiency - A.H. Mohammad; E. Rohr; A. Moise; R.M. Abdulsalam; W. Davalan; A. Rizzolo; A.S. Liberman; C. Goudie; L. Palma; W.D. Foulkes (ESMO Gastrointestinal Oncology)
Background: Underdiagnosis of constitutional mismatch repair deficiency (CMMRD) syndrome leads to suboptimal cancer surveillance and management of CMMRD patients. Assessing pitfalls that led to the misdiagnosis of CMMRD is important to improve care trajectories, and to highlight the importance of accurate molecular and pathology-based assessment of patients presenting with CMMRD-associated features. Materials and methods: A retrospective chart review of two patients with molecularly confirmed CMMRD ascertained through the Medical Genetics service of the McGill University Health Centre (MUHC) was conducted to study the pathway and pitfalls to diagnosis. Records were reviewed and summarized as timelines to depict important events relating to diagnosis and management of CMMRD patients. Results: Unfamiliarity with CMMRD contributed to a diagnosis delay and initiation of CMMRD-specific surveillance. Pitfalls along the diagnostic pathway included inaccurate clinical information relayed to pathologists, unfamiliarity with CMMRD-defining features on immunohistochemistry (IHC) analyses, IHC variability and unreliability, and lack of awareness of the pivotal role for medical genetics in the diagnosis of CMMRD. Conclusions: Improved awareness of CMMRD in patients presenting with CMMRD-associated features can help guide IHC analysis and expedite referral to medical genetics for accurate molecular diagnosis. Consequently, timely CMMRD diagnosis improves surveillance and patient management and allows for appropriate genetic counseling for family members.